The given differential equation is
"e^xdx+(e^xcoty+2ycosecy)dy = 0."Now if we multiply both sides by "siny , we \\space get"
"e^xsiny \\space dx + (e^xcoty *siny + 2y *cosecy*siny)\\space dy =0\\\\or, e^xsiny \\space dx + (e^xcosy + 2y) \\space dy=0\\\\or, e^x siny \\space dx +e^xcosy \\space dy+ 2ydy = 0\\\\"
Now this is much more simplified form of the given differential equation and can be written as
"d(e^xsiny)+ d(y^2) = 0"
Now integrating botth sides we get,
"\\int d(e^xsiny) + \\int d(y^2) = C" ( where C is a constant of integration)
"e^xsiny + y^2 = C"
"\\therefore" The required solution is
"e^xsiny + y^2 = C"
Comments
Leave a comment